Bacterial biomasses and activities in the Northwest African upwelling region - Tjhing Lok Tan; Hans-Jürgen Rüger (PANGAEA, 1989)
During the extquotesingleMeteor extquotesingle expedition SUBTROPEX extquotesingle82, sediment samples were taken at 14 stations in different water depths at 35, 29, 25, 21 and 17 °N, and measurements of bacterial biomasses and activities were carried out in these different upwelling-intensity areas. Highest densities and biomasses by AODC (2.2 x 10**8 cells, corresponding to 14.8 μg C/g sediment dry wt) were recorded at 21 °N, year-round upwelling, at 1200 and 800 m, but at 500 m biomass was still 4.3 μg C/g dry wt. Relatively high densities and biomasses (6.5 and 6.8 μg C/g dry wt) were found at 17 °N, upwelling mostly in winter and spring, at 1200 and 800 m. AODC were 2 to 3 orders of magnitude higher than viable counts, incubation at 2 or 20 °C. For deep-water sediments, counts at 2 °C were higher than at 20 °C. Biomass and ATP concentrations were highest in the 0 to 2 cm sediment layers; they decreased with sediment depth. Bacterial biomasses were correlated with organic carbon and ATP concentrations. The fractions of Bacterial ATP were calculated to be 2 to 24% of ATP-biomass. On the basis of organic carbon, however, fractions of Bacterial Organic Carbon were only 0.02 to 0.06%. For microbial communities, the conversion factor 0.004 for BOC to BATP seems 2 orders of magnitude too high. Maximum AEC ratios of 0.53 to 0.70 were found at 21 and 17 °N; the other stations had AEC ratios of 0.21 to 0.47. Numbers of bacteria with respiratory ETS were between 0.5 and 10.5 % of AODC. An exception was the shelf station at 35 °N with 34.2% of AODC.
Supplement to: Tan, TL; Rüger, H-J (1989): Benthic studies of the Northwest African upwelling region: Bacteria standing stock and ETS-activity, ATP-biomass and Adenylate Energy Charge. Marine Ecology Progress Series, 51, 167-176, https://doi.org/10.3354/meps051167